The Right to Nationality as a Human Right – The Example of the Integration of Refugees in the Republic of Serbia and Solutions de lege lata and de lege ferenda - Stojanović, Bojan; Ivanović, Aleksandar R. (Zbornik Instituta za kriminološka i sociološka istraživanja, 2019)
The authors deal with the issue of the right of refugees to obtain nationality in the receiving state, with a special focus on the legislation of the Republic of Serbia. In this regard, the authors first start from the right to nationality, pointing out the most important international legal documents that prescribe this human right, as well as international conventions that regulate the issue of the status of stateless persons and the resolution of the phenomenon of statelessness. In the central part of the paper, the authors address the issue of the rights of refugees to nationality through an analysis of the basic international documents that regulate this issue and, in parallel, illustrate the solutions to this issue in the national legislation of the states in the environment. In the final part of the paper, the authors analyse the current legislation of the Republic of Serbia, which regulates the situation of refugees, as well as the issue of acquiring nationality, noting that the existing legal framework of the Republic of Serbia regarding nationality is not in accordance with international treaties when it comes to the refugee's ability to obtain nationality of the Republic Serbia. By the end of the work, the authors offer a proposal for changes to the domestic legislation in order to give the refugees the possibility of acquiring the nationality of the Republic of Serbia, that is, enable the exercise of the right to nationality as the highest degree of integration in Serbian society.